2005
DOI: 10.1039/b509094f
|View full text |Cite
|
Sign up to set email alerts
|

A novel bis-phenanthridine triamine with pH controlled binding to nucleotides and nucleic acids

Abstract: The new bis-phenanthridine triamine is characterised by three pK(a) values: 3.65; 6.0 and >7.5. A significant difference in the protonation state of at pH = 5 (four positive charges) and at pH = 7 (less than two positive charges) accounts for the strong dependence of -nucleotide binding constants on nucleotide charge under acidic conditions, whereas at neutral pH all -nucleotide complexes are of comparable stability. All experimental data point at intercalation as the dominant binding mode of to polynucleotide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 59 publications
(42 citation statements)
references
References 44 publications
1
40
0
1
Order By: Relevance
“…The advantages in respect to commonly used synthesis [11,12,15] were demonstrated by easy and efficient modulation of bis-phenanthridine structure starting from the only two building blocks (glycine and phenanthridine-L-alanine), which allowed simple tuning of the cavity size between phenanthridine subunits as well as intramolecular rigidity of compounds. Spectrophotometric studies revealed that in biologically relevant medium bisphenanthridine derivatives exhibit significant intramolecular interactions strongly dependent on the rigidity and length of the peptide linker.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The advantages in respect to commonly used synthesis [11,12,15] were demonstrated by easy and efficient modulation of bis-phenanthridine structure starting from the only two building blocks (glycine and phenanthridine-L-alanine), which allowed simple tuning of the cavity size between phenanthridine subunits as well as intramolecular rigidity of compounds. Spectrophotometric studies revealed that in biologically relevant medium bisphenanthridine derivatives exhibit significant intramolecular interactions strongly dependent on the rigidity and length of the peptide linker.…”
Section: Discussionmentioning
confidence: 99%
“…[12] Our recent results have pointed out that selectivity of bis-phenanthridine derivatives toward various DNA/RNA sequences could be controlled by the steric effects [13,14] or by electrostatic interactions with DNA/RNA backbone and/or nucleobases. [15,16] However, the efforts to upgrade already promising molecules quite often led to longer and more complicated synthetic pathways. Therefore, the strategy of convergent synthesis, which will retain structural features of successful molecules but allow significantly easier and faster modulation of active structure, would allow fine tuning of selectivity and/or other tasks of a novel, small molecules to be done by reasonable time and effort investment.…”
Section: Introductionmentioning
confidence: 99%
“…The absorbance at 260 nm was continuously monitored for solutions of each DNA (100 lM) in the absence and presence of different concentration of [Ru(bpy) 2 (appo)] 2+ in SSC buffer (150 mM NaCl, 15 mM sodium citrate, pH 7.0) for CT-DNA and SC buffer (15 mM sodium citrate, pH 7.0) for poly(dA) Á poly(dT) and poly(dG) Á poly(dC) [35,36]. The temperature of the each sample was increased by 1.0°C min À1 for CT-DNA and 0.5°C min À1 for poly(dA) Á poly(dT) and poly(dG) Á poly(dC).…”
Section: Dna-binding Experimentsmentioning
confidence: 99%
“…15 In our very recent studies, we noticed that electron-rich substituent as urea attached at 8-position of phenanthridine can induce intriguing fluorimetric specificity against AT (emission increase) and GC (emission quenching) basepairs, which was not previously reported for phenanthridine derivatives. 16 All aforementioned inspired us to design novel phenanthridine derivatives equipped at 3 and/or 8 positions with substituents which can actively participate in non-covalent binding to DNA/RNA, due to steric and electronic properties differentiate between various secondary structures and/or basepair composition of polynucleotide and report that recognition in the spectroscopically feasible form.…”
Section: Introductionmentioning
confidence: 96%